Myths and Misinformation: An Analysis of Text Messages Sent to a Sexual and Reproductive Health Q&A Service in Nigeria. Issue 1 (8th March 2016) - Blanc, Ann K.; Glazer, Kimberly; Ofomata‐Aderemi, Uju; Akinfaderin‐Agarau, Fadekemi
Abstract : The almost 50 million young people aged 10–24 in Nigeria face many challenges to their sexual and reproductive health (SRH). MyQuestion is a platform that allows young people to ask SRH questions via text message. Trained counselors provide responses using a database of answers to frequently asked questions or customized replies. We analyze the content of more than 300, 000 text messages received by the service since 2007 to address three questions: which health topics are most frequently submitted to the MyQuestion service; what kinds of questions are asked about these topics; and what language is used to convey the questions? We find a substantial unmet need for basic SRH information, with users' questions communicated in ways that convey considerable confusion, misinformation, and urgency. The analysis can be used to improve similar Q&A services and to improve the provision of SRH services for young people more generally.